Pengelolaan Sampah di Perguruan Tinggi Sesuai Konsep Green Campus (Studi Kasus: Universitas Respati Yogyakarta) - Nur Alvira Pascawati; Elisabeth Deta Lustiyati; Jati Untari; Dea Putri Ramadanti (Dinamika Lingkungan Indonesia, 2023)
The expansion and growth of Higher Education in Indonesia are very rapid with a large population, large area, and dense activity, resulting in significant waste generation. This study was to analyze and plan waste management according to the green campus concept. This research uses a descriptive explorative with a case study strategy at Universitas Respati Yogyakarta. The sample is all waste generated in the campus and the research instrument uses 2 guidelines: measurement of waste generation and composition refers to the SNI and waste management analysis based on guidelines from UI GreenMetric. The results showed that the generation and volume of waste were above the SNI values. The waste containers provided do not meet SNI: volume, number, color, and several waste collection tools. The campus has a program to reduce the use of paper and plastic, but it has not been maximized because there is no recycling program, >75% of organic waste has not been handled, there is no handling of B3 waste and the method of disposing of liquid waste is still conventional. The conclusion is that handling waste on site is a step that must be carried out before being disposed of in a container.